Influence of Potting Mixture on Growth and Quality of Sandalwood (Santalum album L.) Seedlings - Mohapatra, S. R.; Bhol, N.; Nayak, R. K. (Indian Forester, 2019)
The investigation on influence of potting mixture on growth and quality of Sandalwood (Santalum album L.) seedling was carried out at College of Forestry, Orissa University of Agriculture and Technology (O.U.A.T), Bhubaneswar, India during 2014 â€“ 2015 with the objective to improve the quality of planting material in short period. This investigation was necessary because Sandalwood is the second most expensive wood in the world, next to the African Blackwood (Dalbergia melanoxylon), but the plant is a hemi-parasitic and growth of seedling is slow. In the experiment, potting mixtures were prepared with sand, red soil, FYM, perlite, vermicompost, neem cake and karanj cake in 19 different combinations and filled in 9â€x5â€ size black polythene bags in the month of June, 2014. The new germinants (2 months after sowing of seeds) of Sandalwood, which were sown in nursery in the 2nd week of May, 2014 were transplanted in these filled in polythene bags in 1st week of July, 2014. In each polythene bag, one Arhar (Cajanus cajan) plant as primary host plant was grown by sowing seeds at the same time. The growth and quality of Sandalwood seedlings were evaluated upto 270 days after sowing. The potting mixture sand + red soil + vermicompost in 1:1:1 ratio recorded significantly higher height (43.53cm), collar diameter (4.06mm), number of leaves per plant (51.43), branch number (4.71), shoot biomass (12.50g), root biomass (2.95g), total biomass (15.45g) and quality index (1.03) at 270 DAS.